(untitled) (Kinesiology, 2020)
We investigated whether there is more matching in personality traits, emotional intelligence and social skills in better–performing dance couples than in their less successful counterparts and if better and worse dancers individually have more equivalent personality traits, emotional intelligence and social skill. 30 dance couples (i.e. 30 male and 30 female dancers) performing Latin and standard dances at a competitive level were included in the study. Among the measured metrics were: personality traits (using the Big Five Questionnaire), social skills (using the Interpersonal Skills Questionnaire) and emotional intelligence (using the Emotional Competence Questionnaire). When comparing differences between couples, results showed that better dance couples are more orderly, agreeable and conscientious than worse dance couples. Whereas worse dance couples seem to be more open. When comparing differences between dancers, results showed that better–performing dancers tend to be older, more experienced, with a higher »competitive mileage« and better–trained bodies, are more diligent, firmly believe in their success, are confident in attaining their goals and are more highly motivated. They are also more emotionally stable – a trait that stems from their maturity and long years of competing. Findings obtained by our study will certainly allow us to view competitive dancers from a different, as of yet undiscovered and potentially deeper viewpoint of psychology. One of the practical aspects of our research lies in understanding how to keep dance couples together longer, allowing dancers to perform in unison for longer periods than would be otherwise possible.